Feed Rate Influence on Motion Error Characteristics of CNC Vertical Milling Machine - Ahmad Bakir, Azman; Ahmad, Zainal Abidin; Mohamed, Mazlan; Hassan, Mohd Nor Hakim; bin Ahmad, Muhamad Iqbal (Trans Tech Publications, 2013)
The increasing number of the Computer Numerical Control (CNC) machines’ usage in the manufacturing field appears to suggest that they are expected to be in good running condition. Machine tools such as CNC vertical milling machines are meant to produce precise work parts. Motion errors are factors which can directly affect the accuracy of the machine. This study presents an opportunity for interested parties to understand the characteristics of motion errors that exist in the CNC vertical milling machines with different feed rate settings. The purpose of this project is to find out any abnormalities apparent to the machine performance as the feed rate setting is increased. The motion errors of the CNC machines were examined by using a measuring device, namely Double Ball Bar (DBB). This equipment is designed to examine machine performance by measuring the accuracy of its movements. This device, which has two balls of identical size at the end of the bar, was mounted on a spindle and onto a special holder which is mounted on the working table. The machine is programmed to move in a circular motion, clockwise and anticlockwise in three planes, XY, YZ and ZX. Any deviation from the standard data will represent the imperfection of the machine’s condition, especially mechanical components such as the slide bearing, spindle bearing or servo motor responses. By knowing the most significant error origin, the corrective countermeasures can then be carried out.